Durability of Sulfonated Aromatic Polymers for Proton-Exchange-Membrane Fuel Cells - Hou, Hongying; Di Vona, Maria Luisa; Knauth, Philippe (ChemSusChem, 2011)
As a key component of proton‐exchange‐membrane fuel cells (PEMFCs), proton‐exchange membranes (PEMs) must continuously withstand very harsh environments during long‐term fuel cell operations. With the coming commercialization of PEMFCs, investigations into the durability and degradation of PEMs are becoming more and more urgent and interesting. Herein, various recent attempts and achievements to improve the durability of sulfonated aromatic polymers (SAPs) are reviewed and some further developments are predicted. Extensive investigations into inexpensive SAPs as alternative electrolyte membranes include modification of available polymer materials; design, synthesis, and optimization of new macromolecules; durability testing; and exploring the degradation mechanisms. Long‐lasting power: With the coming commercialization of proton‐exchange‐membrane fuel cells (PEMFCs), investigations into the durability and degradation of PEMs are more urgent (see picture; OCV=open‐circuit voltage). In recent years, increasing attention has been paid to sulfonated aromatic polymers, which are inexpensive, easily available, and promising for fuel cell applications, and the subject of this review.